Analysis of Al2O3-Cu nanofluid flow behaviour over a permeable moving wedge with convective surface boundary conditions - Anuar, Nur Syazana; Bachok @ Lati, Norfifah; Md Arifin, Norihan; Rosali, Haliza (Elsevier, 2021)
This research examines the steady flow and heat transfer over a moving wedge in Al2O3-Cu/water nanofluid with convective boundary condition. The governing partial differential equations (PDEs) are converted into nonlinear ordinary differential equations (ODEs) using similarity variables and then numerically solved using the built-in Matlab function (bvp4c).The impacts of wedge parameter, Biot number parameter, nanoparticle volume fraction, suction parameter together with moving parameter are investigated and presented graphically. The numerical evidences exhibit the existence of non-unique solution only when the free stream and wedge moves in the opposing direction. The range of similarity solutions to exist is found to be larger for hybrid nanofluid compared to nanofluid. Also, increasing values of wedge parameter and nanoparticle volume fraction can delay the boundary layer separation. To identify which solution is physically stable, we performed the stability analysis. The results indicate that the first solution is stable.